Long-Term Outcome of Acute Spinal Cord Ischemia Syndrome - Krassen Nedeltchev; Thomas J. Loher; Frank Stepper; Marcel Arnold; Gerhard Schroth; Heinrich P. Mattle; Matthias Sturzenegger (2004)
Background and Purpose— Current knowledge of long-term outcome in patients with acute spinal cord ischemia syndrome (ASCIS) is based on few studies with small sample sizes and <2 years’ follow-up. Therefore, we analyzed clinical features and outcome of all types of ASCIS to define predictors of recovery. Methods— From January 1990 through October 2002, 57 patients with ASCIS were admitted to our center. Follow-up data were available for 54. Neurological syndrome and initial degree of impairment were defined according to American Spinal Injury Association (ASIA)/International Medical Society of Paraplegia criteria. Functional outcome was assessed by walking ability and bladder control. Results— Mean age was 59.4 years; 29 were women; and mean follow-up was 4.5 years. The origin was atherosclerosis in 33.3%, aortic pathology in 15.8%, degenerative spine disease in 15.8%, cardiac embolism in 3.5%, systemic hypotension in 1.8%, epidural anesthesia in 1.8%, and cryptogenic in 28%. The initial motor deficit was severe in 30% (ASIA grades A and B), moderate in 28% (ASIA C), and mild in 42% (ASIA D). At follow-up, 41% had regained full walking ability, 30% were able to walk with aids, 20% were wheelchair bound, and 9% had died. Severe initial impairment (ASIA A and B) and female sex were independent predictors of unfavorable outcome ( P =0.012 and P =0.043). Conclusions— Considering a broad spectrum of clinical presentations and origins, the outcome in our study was more favorable than in previous studies reporting on ASCIS subgroups with more severe initial deficits.